"Attitude of practicing primary school teachers towards science teaching " (2009)
Inculcating in Nigerian children the spirit of inquiry and creative thinking through science teaching is one of the objectives of primary education in Nigeria. Thus, focusing a research study which examined the attitudes of practicing teachers at this level of education towards the teaching of this subject should be of paramount importance. This study also constructed a questionnaire on “attitude towards science teaching” and used it to determine the attitude of teachers in primary schools located in Ibadan, Nigeria towards science teaching; and whether any significant gender-group difference exist in the teachers’ attitude. It made use of 50 primary school teachers who responded to a 15 item valid and reliable questionnaire developed by the researcher. Data analysis involved the use of percentages and chi-square statistics. The results showed that the teachers tend to exhibit negative attitude towards science teaching, and there was also distinct attitude towards science teaching according to their gender. The implications of these results for teacher in-service programmes organizers as well as curriculum developers include creation of courses that could help practicing teachers of science imbibe positive attitude towards the subject as well as help them to understand the effect which teachers’ negative attitude towards his/her teaching could have on the learners